An Investigation of the Iraqi High School Students’ Attitudes towards Peer-Peer and Teacher Feedback - Alzurf, Ali Falah Hasan; Ameen, Badr Jaafar; Al-jashami, Abdullah Abbas (International Journal on Integrated Education, 2024)
Peer feedback is when students provide one another with feedback on their work or performance. Teacher feedback is a powerful pedagogical tool for promoting interaction in educational guidance between teachers and students. Thus, this quantitative research was carried to investigate Iraqi high school students’ perspectives toward peer-peer feedback and teacher feedback. To collect the data, the peer-peer feedback questionnaire and teacher feedback questionnaires were used. The data analysis revealed that a majority of the students exhibited apprehension towards providing unsuitable remarks about their peers. Furthermore, it was disclosed that the majority of the participants exhibited favorable dispositions towards teacher comments. No significant correlation was observed between students’ perceptions on peer-peer feedback and instructor feedback. The results of this study have the potential to be advantageous for both educators and learners.